PROJECT BASED LEARNING: A REVIEW OF LITERATURE ON ITS OUTCOMES AND IMPLEMENTATION ISSUES - Ciptro Handrianto; Muhammad Arinal Rahman (LET: Linguistics, Literature and English Teaching Journal)
Project-Based Learning is gaining popularity in development projects and pedagogic development. The objective of the use the PBL in a classroom is to give students a meaningful experience in learning. This paper will discuss the PBL based on constructivism theory and experiential theory were discussed to give the idea constraint to the use of the PBL. Furthermore, the study will also discuss the implementation of PBL. It is found that some studies have showed positive effect and also it may develop students’ critical thinking and learning attitudes. However, there are several issues regarding the implementation like students acknowledge that the knowledge of today's limited technology changes has prevented them from producing good design ideas.